Insulin encapsulation in reinforced alginate microspheres prepared by internal gelation - Silva, Catarina M. (2006)
Insulin-loaded alginate microspheres prepared by emulsification/internal gelation were reinforced by blending with polyanionic additive polymers and/or chitosan-coating in order to increase the protection of insulin at simulated gastric pH and obtain a sustained release at simulated intestinal pH. Polyanionic additive polymers blended with alginate were cellulose acetate phtalate (CAP), Eudragit® L100 (EL100), sodium carboxymethylcellulose (CMC), polyphosphate (PP), dextran sulfate (DS) and cellulose sulfate (CS). Chitosan-coating was applied by using a one-stage procedure. The influence of additive polymers and chitosan-coating on the size distribution of microspheres, encapsulation efficiency and release profile of insulin in simulated gastrointestinal pH conditions was studied. The mean diameter of blended microspheres ranged from 65 to 106 [mu]m and encapsulation efficiency of insulin varied from 14 to 100%, reaching a maximum value when CS and DS were incorporated in the alginate matrix. Insulin release, at pH 1.2, was almost prevented by the incorporation of PP, DS and CS. When uncoated microspheres were transferred to pH 6.8, a fast dissolution occurred, independently of the additive polymer blended with alginate, and insulin was completely released. Increasing the additive polymer concentration in the alginate matrix and/or chitosan-coating the blended alginate microspheres did not promote a sustained release of insulin from microspheres at pH 6.8.